2020
DOI: 10.1093/scan/nsaa050
|View full text |Cite
|
Sign up to set email alerts
|

Affective brain patterns as multivariate neural correlates of cardiovascular disease risk

Abstract: Abstract This study tested whether brain activity patterns evoked by affective stimuli relate to individual differences in an indicator of pre-clinical atherosclerosis: carotid artery intima-media thickness (CA-IMT). Adults (aged 30–54 years) completed functional magnetic resonance imaging (fMRI) tasks that involved viewing three sets of affective stimuli. Two sets included facial expressions of emotion, and one set included neutral and unpleasant images from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 58 publications
1
26
1
Order By: Relevance
“…In this regard, specific task-evoked fMRI measurements that directly assess the neural reactivity during cognitive evaluation [27][28][29] could help raise the overall predictive power. For example, we recently showed that brain activation patterns during affective information processing tasks predict an important portion of individual differences of cardiovascular disease risk factors, a finding that we could not have reached had not we used the appropriate and specific task fMRI experiment [30]. Additionally, increasing both spatial resolution to better capture features of structural-functional variation [31] and temporal resolution for a more accurate decoding of the underlying brain dynamics [32] could be valuable and complementary sources of cognitive performance correlation.…”
Section: Discussionmentioning
confidence: 87%
“…In this regard, specific task-evoked fMRI measurements that directly assess the neural reactivity during cognitive evaluation [27][28][29] could help raise the overall predictive power. For example, we recently showed that brain activation patterns during affective information processing tasks predict an important portion of individual differences of cardiovascular disease risk factors, a finding that we could not have reached had not we used the appropriate and specific task fMRI experiment [30]. Additionally, increasing both spatial resolution to better capture features of structural-functional variation [31] and temporal resolution for a more accurate decoding of the underlying brain dynamics [32] could be valuable and complementary sources of cognitive performance correlation.…”
Section: Discussionmentioning
confidence: 87%
“… El Kissi et al , 2015 ; Trumpff et al , 2019 ) and genetics ( Flint and Munafò, 2013 ). Contributions in the current special issue similarly reflect the massive shift toward more sophisticated computational methods in order to test some of the original claims and revisit findings based on small samples from early health neuroscience ( Gianaros et al , 2020 ) and fill in gaps in longstanding models of health ( Berkman, 2018 ; Cosme et al , 2020 ). To the extent that innovative solutions to ‘big data’ can be refined at the level of the brain, these advances will also be helpful to understanding biomarkers of health risk.…”
Section: New and Continuing Emphases: Where Can The Scan Community Comentioning
confidence: 99%
“…Illustrative examples from the current special issue that capitalize on this perspective include those that use state-of-the-science analytical approaches (e.g. machine learning to identify multivariate patterns of neural activity) to predict a host of the most pressing health issues facing society today: cardiovascular disease ( Gianaros et al , 2020 ), obesity ( Stice et al , 2019 ; Cosme et al , 2020 ; Donofry et al , 2020 ; Verstynen et al , 2020 ) and physical pain ( Reddan et al , 2020 ). Similar approaches help us understand links between brain patterns of activity to emotional content and systemic inflammation, a key biological mediator linking psychological experience and health ( Alvarez et al , 2020 ), or to health messages and population-level sharing of the information ( Dore et al ., in press ).…”
Section: Health Neuroscience 20mentioning
confidence: 99%
See 2 more Smart Citations